Therapeutic efficacy of monoclonal antibodies and antivirals against SARS-CoV-2 Omicron BA.1 in Syrian hamsters - Uraki, Ryuta; Kiso, Maki; Imai, Masaki; Yamayoshi, Seiya; Ito, Mutsumi; Fujisaki, Seiichiro; Takashita, Emi; Ujie, Michiko; Furusawa, Yuri; Yasuhara, Atsuhiro; Iwatsuki-Horimoto, Kiyoko; Sakai-Tagawa, Yuko; et al. (Nature microbiology, 2022)
The spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the major antigen stimulating the host’s protective immune response. Here we assessed the efficacy of therapeutic monoclonal antibodies (mAbs) against Omicron variant (B.1.1.529) sublineage BA.1 variants in Syrian hamsters. Of the FDA-approved therapeutic mAbs tested (that is, REGN10987/REGN10933, COV2-2196/COV2-2130 and S309), only COV2-2196/COV2-2130 efficiently inhibited BA.1 replication in the lungs of hamsters, and this effect was diminished against a BA.1.1 variant possessing the S-R346K substitution. In addition, treatment of BA.1-infected hamsters with molnupiravir (a SARS-CoV-2 RNA-dependent RNA polymerase inhibitor) or S-217622 (a SARS-CoV-2 protease inhibitor) strongly reduced virus replication in the lungs. These findings suggest that the use of therapeutic mAbs in Omicron-infected patients should be carefully considered due to mutations that affect efficacy, and demonstrate that the antiviral compounds molnupiravir and S-217622 are effective against Omicron BA.1 variants. Therapeutic monoclonal antibodies (COV2-2196/COV2-2130) inhibited the replication of SARS-CoV-2 Omicron BA.1 but not BA.1.1 variants in the lungs of Syrian hamsters. Antivirals (molnupiravir and S-217622) were effective against BA.1 in hamsters.